(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The birth of a baby is usually attractive to the parents,but not for the eldest child. The eldest child will feel jealous, especially when he or she saw his little brother or sister were in the arms of their parents like the eldest child’s experience. The eldest child would feel threatened by the presence of the baby that may receive more attention. Sibling rivalry or jealousy to his little brother could make the eldest child hates or even hostile to his little brother. The factor that affecting sibling rivalry is type of parenting that applied by the parents. Purpose: to know the relationship between democratic parenting with sibling rivalry in preschool children in TK Kuncup Harapan Panggungharjo Sewon Bantul Method: this research is a kind of analytic survey with cross sectional method. Population in this research are parents of the children in TK Kuncup Harapan, to decide the sampling using purposive sampling method and there are 35 respondents. Instruments of this research using two questionnaires, democratic parenting questionnaires and sibling rivalry among the preschool children. The data analysis using chi square. Result: The analysis result using chi square method is x1 2count > x2 table = 6,818> 3,84 and p value 0,024 <0,05 and prevalence ratio 3 (CI 1.2815 - 7.3386) so the H0 is rejected Conclusion: There is a relationship between democratic parenting with sibling rivalry in preschool age children and the children whose parents apply democratic parenting have risk three times higher to have sibling rivalry than children whose parents apply democratic parenting. Keywords: democratis parenting, sibling rivalry